STUDI PERBANDINGAN POLA ALOKASI LAHAN, PENGELUARAN BERAS DAN POLA KONSUMSI PANGAN ANTARA PETANI UBI KAYU DI DESA PELAKSANA DAN NON PELAKSANA PROGRAM MP3L DI KABUPATEN LAMPUNG SELATAN - M Imacullata Santa De Vega Indiako; R Hanung Ismono; Achdiansyah Soelaiman (Lampung University, 2014)
The purposes of this research are to compare: the allocation of land of cassava, the spending of rice and food consumption patterns, between cassava farmers in the village of implementers and non-implementers of the MP3L (Model Pengembangan Pangan Pokok Lokal) Programme in South Lampung regency. The research was conducted in Pancasila village and Negara Ratu village, Natar district, South Lampung regency. The number of respondents in the research is 44 people, consisting of 22 cassava farmers in the Pancasila village and 22 of cassava farmers in Negara Ratu village. Analysis method used in this study is a quantitative descriptive. The results showed that: the allocation of land to plant cassava in Negara Ratu village is wider than in Pancasila village. The land allocation for planting cassava likely caused by the need of farmers to consume cassava and the guarantee of the markets. The average household rice spending at Pancasila village was Rp858,303.03 per capita per year, while the average household rice spending at Negara Ratu village was Rp1,044,121.77 per capita per year. Significant of that difference value was caused by the customs of households at Pancasila village to consume cassava by processing daily, excluding Beras Siger. The desirable food pattern (PPH) score of cassava farmers at Pancasila village (87.8) was higher than PPH score of cassava farmers at Negara Ratu village (80.5). Reduction of rice has occurred at Pancasila village, but it was not caused by substitution of rice by Beras Siger. Key words: cassava farmers, consumption patterns, land allocation, MP3L